Aplikasi larutan EMOVA daun kelor (Moringa oleifera) dan daun afrika (Vernonia amygdalina) dalam menekan mortalitas ikan nila (Oreochromis niloticus) pada simulasi transportasi - Sunarno Sunarno; Eko Purnomo; Khunfaya Firnanda Putri Rossida; Maulida Aqlinia; Falasifah Falasifah; Mamluatul Lailiyah (Jurnal Biologi Tropika, 2019)
Fish transportationis logistical aspect of the fishery business. Wrong procedures in handling fish during transportation can trigger stress. Herbal ingredients such as kelor (Molinga oleifera) and afrika leaf (Vernonia amygdalina) have the potential to overcome stress on fish. Both types of herbal ingredients contain compounds of flavonoids and phenols that have the potential to be analgesik. The purpose of this study was to analyze the analgesik effect of kelor and afrika leaf extract to nila fish (Oreochromis niloticus) using transportation simulation model. The experimental design was usedcomplete randomized design with four treatments, including the cold temperature of 10ºC (L0), the extract solution of kelor and afrika leaf was use ratio 1:1 with concentrations of 10% (L1), 20% (L2) and 30% (L3) solution. The main parameters observed were viability and mortality. The experiment results showed that the treatment of L1 and L2 was not significantly different with the control, L2 treatment was not significantly different with L3 but L3treatment was significantly different with kontrol and L1. The viability of the L3 treatment is higher than control and treatment of L1, as well as for mortality parameters. The conclusion of this research is, extract of kelor and afrika leaf combination with 1:1 ratio at 30% concentration in transportation simulation model can cause high viability value and able to depress mortality. The results of this study can be used as a solution to fish mortality due to stress and handling of fish based on animal welfare principle during transportation.